Success rate and neonatal morbidities associated with early extubation in extremely low birth weight infants - Al Faleh, Khaled (Medknow Publications & Media Pvt Ltd, 2011)
BACKGROUND AND OBJECTIVES: Mechanical ventilation improves survival of preterm infants with respiratory failure. The aim of this study was to determine the success rate and short-term neonatal morbidities of early extubation in extremely low birth weight (ELBW) infants in a tertiary care neonatal intensive care unit (NICU). DESIGN AND SETTING: Retrospective cohort study of ELBW infants admitted to a tertiary. neonatal intensive care referral unit from January 1(st) to December 31(st), 2005. PATIENTS AND METHODS: The primary outcome was the success rate of early extubation in ELBW infants who were intubated at delivery, extubated in the first 48 hours of life, and did not require reintubation within 72 hours following extubation. RESULTS: Thirty of the 95 eligible infants were extubated early; of these 30 infants, 24 (80%) had a successful extubation. Infants extubated early had a higher mean birth weight (855 vs 745 g; P<.0001) and gestational age (27.3 vs 25.6 weeks; P<.0001). ELBW infants who were extubated early had lower rates of death (relative risk [RR], 0.05; 95% CI, (0.0, 0.79); P=.003), intraventricular hemorrhage (IVH) (RR, 0.23; 95% CI, 0.08, 0.70; P=.008), and patent ductus arteriosus (PDA) (RR, 0.76; 95% CI, 0.60, 0.98; P=.03) compared with those who remained ventilated beyond the first 48 hours of life. CONCLUSION: The rate of successful early extubation in our unit exceeded the sole previously reported rate. Successful early extubation was associated with lower rates of death, IVH, and PDA in ELBW infants.